Gastropod community structure on seagrass beds in Bahoi Village, North Minahasa - Tualangi, Jehezkiel Timotius; Rangan, Jety K.; Sangari, Joudy R. R.; Rondonuwu, Ari B.; Manu, Gaspar D.; Kondoy, Khristin I. F. (Jurnal Ilmiah Platax, 2023)
The village of Bahoi has a vast expanse of seagrass meadows of approximately 16.50 Ha, located between mangrove and coral reef ecosystems. This study aims to inventory the gastropod species in the seagrass meadow of Bahoi village waters and to determine the gastropod community structure through analysis of species density, relative density, species diversity index, and dominance index. The method used was a transect line method along 50 meters and a 1x1m quadrat pulled towards the sea, repeated three times during low tide. A total of 117 individuals were found, belonging to 26 species (11 families and 17 genera) of gastropods in the seagrass meadow of Bahoi village coastal waters. Based on the results, the highest density value was 1.10 ind/m2 with a relative density of 28.20%. Based on the analysis, the dominance index (D) of gastropods in the seagrass meadow of Bahoi village coastal waters was low, with values of D = 0.019 to 0.041, indicating that there was no specific species dominance in the seagrass meadow of Bahoi village coastal waters. This has an effect on the diversity index with a value of H' = 2.51, which is categorized as moderate. These results show that the diversity of gastropod species in the seagrass meadow of Bahoi village waters is quite diverse due to the absence of specific gastropod species dominance. Keywords: Bahoi, Seagrass Meadow, Gastropods, Community Structure. Abstrak Desa Bahoi memiliki luas hamparan padang lamun ± 16.50 Ha yang berada di antara ekosistem mangrove dan ekosistem terumbu karang. Penelitian ini bertujuan untuk melakukan inventarisasi jenis-jenis gastropoda di hamparan lamun perairan Desa Bahoi, dan mengetahui struktur komunitas gastropoda melalui analisis kepadatan spesies, kepadatan relatif, indeks keanekaragaman spesies, dan indeks dominasi. Metode yang digunakan adalah metode transek garis sepanjang 50 meter dan kuadrat berukuran 1×1m yang ditarik ke arah laut, dan dilakukan ulangan sebanyak 3 kali pada saat air surut.Ditemukan 117 individu yang termasuk ke dalam 26 spesies (11 famili dan 17 genera) gastropoda di hamparan padang lamun perairan pantai desa Bahoi. Berdasarkan hasil penelitian, nilai kepadatan tertinggi sebesar 1,10 ind/m2 dengan kepadatan relatif 28,20%. Berdasarkan hasil analisis, Indeks Dominansi (D) gastropoda di hamparan lamun perairan pantai desa Bahoi tergolong rendah, dengan nilai D=0,019 sampai dengan 0,041 menunjukkan bahwa tidak terdapat dominasi spesies tertentu di hamparan padang lamun perairan pantai desa Bahoi. Hal ini berpengaruh terhadap Indeks Keanekaragaman dengan nilai H’=2,51 sehingga berada pada kategori sedang. Hasil tersebut menunjukkan bahwa keanekaragaman jenis gastropoda di hamparan lamun perairan pantai desa Bahoi cukup beragam dikarenakan tidak adanya dominasi spesies gastropoda tertentu. Kata kunci: Bahoi, Padang Lamun, Gastropoda, Struktur Komunitas